Toggle buckling-restrained brace systems and a corresponding design method for the seismic retrofit of bridge bents. (15th October 2020) - Shi, Yan; Zhong, Zhengwu; Qin, Hongguo; Han, Jianping; Sun, Zhiguo
Highlights: A new configuration of BRBs was utilized to retrofit bridge bents. Toggle buckling-restrained brace systems studied for the first time analytically. A corresponding design method for this system was developed. The failure modes of bridge bents were taken into account. Abstract: Based on the structural fuse concept, easily replaceable fuses are designed to sustain seismic demand and dissipate seismic energy while keeping RC bridge bents elastic, so the retrofitted bents have a very low displacement demand. Buckling-restrained braces (BRBs) are common fuses used in the seismic retrofit of bridge bents. However, the energy dissipation capacity of BRBs cannot be fully utilized under a small displacement if the diagonal or inverted-V configurations are adopted. Combining the structural fuse concept with toggle brace mechanisms, this paper studied a toggle BRB system that can amplify the effect of damper devices. The system was designed to keep the RC bridge bents elastic through the increased energy dissipation capacity of the BRBs. Several key parameters, including the displacement amplification factor and the steel core length-to-total length ratio, were discussed. The admissible values of the displacement amplification factor for different bents were plotted with contour lines. In addition, a displacement-based design procedure was proposed that ensured the bents achieved the target performance under a design-level earthquake. Two design examples were illustrated: a bent that failed in a flexural mode and another bent that failed in a flexural-shear mode. Finally, the feasibility of the design procedure was validated with nonlinear time history analyses.